Legal Securities Against Privacy Data for Covid-19 Patients in Indonesia - Sihombing, Eka N.A.M; Hadita, Cynthia; Adi Syaputra, Muhammad Yusrizal (Veteran Law Review, 2021)
Disclosure issues priva the patient data cov id-19 has a dilemma, on the other hand the patient covid-19 must be protected data privacy of her so as not to spread public consumption because it will be implications negative for patients covid-19 towards economic, social , and -Other if the medical record is disseminated without perse purpose. Thus, the study will also describe a court decision in which a patient sued peme covid 19 Rinta h area who held a press conference on the post itifnya patients covid-19 and also sued one sa tu mass media that reported on k eadaannya. Thus, there are like two sides of a coin, in the other hand  patient data privacy must be protected , but on the other hand, information dissemination d ith patient permission dibutuh right to avoid other people her exposed covid-19 , because it takes trace contacts of patients covid-19 so that the virus does not spread. That way, the privacy protection of Covid-19 patient data needs to be studied to answer this dilemma with the data privacy protection model for Covid-19 patients . The research method used in this research is a normative juridical method using a doctrinal approach. Objective is to familiarize yourself isa setting clicking Enai patient data privacy Covi d -19 in Indonesia and comparative with the protection of the privacy of patient data covid-19 in n egara another. Discussion result study showed that  compassion are, whereas the Constitution (Article 28 G paragraph ( 1 )), Article 57 of the Health Act, and some of international convention  already ratification in Indonesia, also on the core of her had been arranged that the privacy of the patient should be in the case but there is still a central or regional governments that violate the privacy of patients covid-19 with announce very detail about  patient covid-19 data privacy that adversely affects the patient. Refers to protecting the privacy of patient data covid-19 in the EU, UK, US, China, India, Hongkong, Malaysia, and Singapura which ensures it firmly to prevent leakage of data that can be go to the general public so that, right to maintain the privacy of data of covid-19 patient, and the tracking integrated via applications that are already guaranteed securities.